BUILDING RESILIENT DISTRIBUTED DATABASES: MODERN APPROACHES TO HIGH AVAILABILITY - Abhishek Andhavarapu, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Distributed databases form the cornerstone of modern digital infrastructure, supporting critical applications across various sectors including e-commerce, finance, and cloud services. This comprehensive article examines current approaches to enhancing database resilience through multiple strategies. It explores follower-read implementations for optimizing data access patterns and analyzing their impact on system performance and consistency requirements. The article investigates quorum replication mechanisms for maintaining data consistency across distributed nodes, detailing the mathematical relationships that govern read and write operations. It also examines adaptive traffic throttling techniques for managing system load and preventing performance degradation during peak usage periods. Furthermore, the article discusses automated fault detection and recovery systems, highlighting the role of machine learning in identifying and responding to potential system failures. The article concludes by exploring emerging trends in distributed database technology, including the integration of advanced machine learning capabilities, autonomous operations, and edge computing solutions. Throughout the article, particular attention is paid to practical implementation considerations and the trade-offs between consistency, availability, and performance in distributed environments.